Demographic distribution of the Tuareg in the Sahara (Elmergib Journal of Human Sciences, 2024)
The Tuareg are a people of nomadic and sedentary Berbers who live in the Sahara Desert, especially in Algeria, Mali, Niger, Libya and Burkina Faso. They are all Sunni Muslims. We will briefly discuss the history of the Tuareg people of the Sahara, the people who stood in the face of the harshest factors of erosion geographically and historically. Opinions differed about the origin of the Tuareg. We will try to review some of the opinions of historians by looking at who they are, and we will shed light on the population and geographical distribution of the Tuareg, and touch on social customs and also look at their culture, and we will address the political life of the Tuareg people, especially in Mali and Niger.Keywords: Tuareg tribes, Libya, Algeria, Niger, Mali, Sahara.Problem of the study: The problem of the study lies in knowing the historical origins of the Tuareg and the cultural aspects of Tuareg society.The importance of the study: Reviving popular culture and paying attention to all its components and elements.Objectives of the study:1- Research into the customs and traditions of the Tariq community.2- Reviving the Tariq heritage as a cultural and cultural resource.Study methodology:In this study, the historical and descriptive approaches were followed.The origins and historical roots of the Tuareg      The Sahara Desert occupies the largest part of North Africa, and it is the largest hot desert in the world, with an area of ​​​​more than 9 million square kilometers, and it is full of oases and oil fields.